2014
DOI: 10.1007/s00264-014-2379-x
|View full text |Cite
|
Sign up to set email alerts
|

Hip reconstruction surgery is successful in restoring joint congruity in patients with cerebral palsy: long-term outcome

Abstract: Early conservative treatment for hip dislocation is helpful, and operative reconstruction should also be scheduled early. Continued surveillance is necessary, and Reimers index is useful for monitoring the development of hip centering. In case of hip pain and femoral head deformity, our long-term study indicates that hip reconstruction surgery as a part of multilevel surgery improves pain and function in patients with CP and Tönnis IV hip dislocation, even if the hip joint is incongruent after operation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 26 publications
6
33
0
1
Order By: Relevance
“…[30]. The slight increase in MP in our study from post-operative to long-term examination was in line with other reports [3]. One-stage reconstruction during SEMLS seems to be the standard procedure [21].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…[30]. The slight increase in MP in our study from post-operative to long-term examination was in line with other reports [3]. One-stage reconstruction during SEMLS seems to be the standard procedure [21].…”
Section: Discussionsupporting
confidence: 93%
“…Long-term examination showed a shift to more congruent and physiological hip-joint morphologies and a significant reduction of pain. Post-operative MP results were in line with the literature [3]. Jozwiak et al reported good results after bony reconstruction of the hip joint with pelvic osteotomy, as described by Dega.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations